Cost-utility analysis of empagliflozin compared with dapagliflozin in patients with type 2 diabetes in China - Huiyuan Zhang; Jiaojiao Chen; Quan Zhao; Bei Zhang (Frontiers in Public Health, 2025)
BackgroundEmpagliflozin, a sodium-glucose cotransporter 2 inhibitor, performs a reduction in the all-cause mortality and cardiovascular mortality in type 2 diabetes mellitus (T2DM) patients compared to dapagliflozin, which has been included in the national volume-based procurement in China. The objective of this study is to evaluate the long-term cost-utility of the addition of empagliflozin (10 mg or 25 mg) versus dapagliflozin (10 mg) in T2DM patients with insufficient control by metformin monotherapy from the perspective of Chinese health care payers.MethodsThe IQVIA CORE diabetes model was used for cost-utility analysis to compare the long-term economics of empagliflozin (10 or 25 mg) versus dapagliflozin (10 mg) respectively. In the two independent analyses, the discount rate was 5% per year, and the utility value was derived from the published literatures. The baseline demographic and biochemical data, as well as treatment efficacy data were obtained from the EMPA-REG MET clinical trial and network meta-analysis, respectively.ResultsCompared with dapagliflozin 10 mg, empagliflozin 10 mg and empagliflozin 25 mg improved the life expectancy by 0.011 and 0.02 years, and improved the quality adjusted life years (QALYs) by 0.011 and 0.02 years, respectively. The total cost of empagliflozin group (10 mg) was 279 Chinese Yuan lower than that of the dapagliflozin group (10 mg), making it an absolutely economical choice. The total cost of empagliflozin (25 mg) was expected to be 1,601 Chinese Yuan higher than dapagliflozin, with an incremental cost-utility ratio (ICUR) of 80,052 Chinese Yuan per QALY, below the set ‌willingness to pay (WTP) threshold of 85,698 Chinese Yuan per QALY.ConclusionFor T2DM patients with insufficient control by metformin monotherapy, the addition of empagliflozin 10 mg showed better efficacy and lower cost compared to dapagliflozin 10 mg, making it an absolutely economical choice. Based on the set WTP threshold, empagliflozin 25 mg was also a more cost-effective treatment option than dapagliflozin from the perspective of Chinese healthcare payers.